How tourism activity shapes travel experience sharing: Tourist well-being and social context - Su, Lujun; Tang, Binli; Nawijn, Jeroen (Annals of tourism research, 2021)
Why people conduct different sharing about their travel is unclear. Understudied areas include the roles of tourism activity type, tourist well-being, and social context. Under the framework of construal level theory, three studies which combined secondary data and experiments revealed that: 1) challenging (relaxing) tourism activities lead to more desirability (feasibility) sharing; 2) eudaimonia (hedonia) occupy the dominant position and mediate the relationship between challenging (relaxing) tourism activity and desirability (feasibility) sharing; and 3) social context induces the transformation of the relationship between eudaimonia and hedonia, and has a significant moderating impact on the mechanism of travel experience sharing type. Theoretical and managerial implications of travel experience sharing type and mutual transformation between eudaimonia and hedonia are discussed. •Travel experience sharing is a heterogeneous activity.•Tourism activity type is the key factor leading to different sharing content.•Tourist well-being is an important mechanism for travel experience sharing.•The relationship between eudaimonia and hedonia transforms across social context.